2024
DOI: 10.1111/raq.12915
|View full text |Cite
|
Sign up to set email alerts
|

Towards sustainable water disinfection with peracetic acid in aquaculture: A review

Dibo Liu,
David L. Straus,
Lars‐Flemming Pedersen
et al.

Abstract: Peracetic acid (PAA) has a long history as an efficacious and eco‐friendly disinfectant. It was first synthesised in 1902, and since then a wide range of applications has been developed in various industries. Aquaculture is a more recent industry wherein the potential of PAA is significant. As the global demand for sustainable development increases, there has likewise been growing interest in using PAA in aquaculture as an alternative to less environmentally friendly practices. PAA has no carcinogenic risk to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 132 publications
0
2
0
Order By: Relevance
“…In a review publication, Lieke et al (2019) discussed the possibility that PAA could be an optimal treatment for velvet disease, which is caused by dinoflagellate parasites belonging to the genera Amyloodinium and Piscinoodinium. Liu et al (2024) discussed research publications in which PAA was shown to be effective against several ectoparasites. Several authors have studied the effectiveness of PAA for controlling Neoparamoeba perurans, the causative agent of amoebic gill disease in marine Atlantic Salmon Salmo salar (Lazado et al 2019(Lazado et al , 2022Furtado et al 2022), and Vannella spp., which are freshwater amoebae that Jensen et al (2020) irritans isolated from marine Gilthead Bream Sparus aurata to study the effectiveness of eight compounds, including PAA, in controlling the parasite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review publication, Lieke et al (2019) discussed the possibility that PAA could be an optimal treatment for velvet disease, which is caused by dinoflagellate parasites belonging to the genera Amyloodinium and Piscinoodinium. Liu et al (2024) discussed research publications in which PAA was shown to be effective against several ectoparasites. Several authors have studied the effectiveness of PAA for controlling Neoparamoeba perurans, the causative agent of amoebic gill disease in marine Atlantic Salmon Salmo salar (Lazado et al 2019(Lazado et al , 2022Furtado et al 2022), and Vannella spp., which are freshwater amoebae that Jensen et al (2020) irritans isolated from marine Gilthead Bream Sparus aurata to study the effectiveness of eight compounds, including PAA, in controlling the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…A relatively new disinfectant to aquaculture that has been investigated with some success is the synergistic combination of peracetic acid (PAA) and hydrogen peroxide (H 2 O 2 ), commonly referred to as "PAA" in the industry. It is considered environmentally friendly because it decomposes into water, oxygen, and acetic acid and could potentially serve as a replacement for formalin (Madsen et al 2000;Pedersen and Henriksen 2011;Liu et al, 2024) if treatment methods are well defined.…”
Section: Introductionmentioning
confidence: 99%